PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS II SDN 011 KEPENUHAN - Ernidawati, Ernidawati; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to improve student learning outcomes in social studies through the application of cooperative learning in class II SDN 011 Kepenuhan. The low student”s learning outcomes of IPS study in class II SDN 011 Kepenuhan caused in learning due to improper teaching model used by teachers in the learning process . Students become passive and lazy to learn because the learning system that occurs simply by using methods lectures, discussion, and assignments. The subjects were students of class II, the number of students all are 13 people consisting of 8 men and 5 women. Instrument and the data used in this study is the observation sheet to measure the activity of the teacher and student activities and tests in the form of daily tests each cycle to measure student learning outcomes. Results of data analysis obtained by the percentage of the activity of teachers at the first meeting of the first cycle of 66.7% with sufficient category and the second meeting of the first cycle of 79.2% with the good category, at the first meeting of the second cycle percentage teacher activity 87.5% with excellent category and the second meeting of the second cycle percentage is 91.7% of teachers activity with excellent category. At the first meeting of the percentage of student activity 58.3% with sufficient category and the second meeting of the first cycle is 70.8% with the good category, at the first meeting of the second cycle the percentage of student activity 79.2% with the good category and the second meeting of the second cycle is 87,5% with excellent category. The score of students in the classical completeness basis is 38.5% (not complete), the first daily test classical completeness of students is 84.6% (completed), and the second daily test classical completeness students is 100% (complete). Based on this study concluded that the implementation of cooperative learning model can improve student’s learning outcomes of IPS study in class II SDN 011 Kepenuhan.Keywords: Cooperative Learning Model, IPS Learning Outcomes